Răspuns :
I (a+b+c)/3=12
II (a+b)/2=10
I a+b+c=12*3 a+b+c=36
II a+b=10*2 a+b=20
20+c=36
c=36-20
c=16
II (a+b)/2=10
I a+b+c=12*3 a+b+c=36
II a+b=10*2 a+b=20
20+c=36
c=36-20
c=16
(a plus b plus c) este egal cu 12
(a plus b) este egal cu 10
(a plus b plus c ) este egal cu 12
(10 plus c ) este egal cu 12
c este egal cu 12 -10 care este egal cu 2
c este egal cu 2
(a plus b) este egal cu 10
(a plus b plus c ) este egal cu 12
(10 plus c ) este egal cu 12
c este egal cu 12 -10 care este egal cu 2
c este egal cu 2